POLITICAL ECOLOGY PROTECTION SPRING WATER IN BATU - Romadhan, Ach Apriyanto; Hardyanti, Winda; Taqwa, Iradhad; Nurkhanifah, Laeli (Government Studies of Muhammadiyah Malang University/AIPPTM, 2020)
Water resources management is a socio-political issue where various interests influence the policy on the protection and utilization of water resources. This research wants to know the government's policies and efforts in protecting water resources amid the rapid industrialization of tourism, along with conflicts due to the use of water resources from a political ecology perspective. This study uses descriptive qualitative research, data collection methods through depth interviews, observation, and documentation. This study shows that the efforts of the Batu City Government in realizing the protection of water resources are not proportional to the acceleration of the conversion of forest and agricultural land functions to support the sustainability of water resources due to the rapid growth of the tourism industry. It can be seen from the inconsistency of policy products, the imbalance in the amount of the budget between the commercialization of land (tourism), and the lack of efforts to conserve springs. As a result, there was resistance from the community in the struggle for access to water resources. Therefore, it is necessary to affirm the boundaries of the utilization of water resources supporting areas, transparency of the sustainability of water resources, and disclosure of information to the public regarding the process of tourism development plans undertaken by investors to facilitate supervision by the public.